Digital Arts Experience: Inovasi Teknologi Sensor Suara dan Sentuh Berbasis IoT untuk Literasi dan Pembelajaran Musik Anak Berkebutuhan Khusus di Sumedang - Iwan Kustiawan; Deasy Rosanti Nurjannah; Ayo Sunaryo; Lilis Widaningsih (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Digital Arts Experience program developed an inclusive music-learning medium for children with special needs using Internet of Things (IoT)-based sound and touch sensors. Activities were conducted at SLB Shapphira Diyanah and Rumah Pintar Ibu Een in Sumedang, involving children, teachers, parents, and community managers. The program comprised needs identification, prototype design and demonstration, teacher training, guided practice with children, and participatory evaluation through observation and stakeholder feedback. Observations indicated more active engagement in exploring sound through movement, vocalization, and touch. Teachers also became more capable of designing multisensory music activities and adapting them to individual needs. Parents reported more varied emotional expression and communication after the sessions. These findings indicate that interactive sensor-based musical devices may support inclusive music learning and gradual technology literacy. However, effectiveness should be examined further using measurable indicators, clearly reported participant data, and a longer period of implementation.